21. SURVEY OF ADVERSE REACTIONS OF ACRIPTEGA ON PATIENTS TREATMENT OF HIV/AIDS IN QUANG NINH PROVINCE IN 2023 (Vietnam Journal of Community Medicine, 2025)
Cross-sectional descriptive study conducted at 11 HIV/AIDS care and treatment facilities in Quang Ninh province. The reported incidence of adverse drug reactions of Acriptega in patients treated for HIV/AIDS is 0.45%. 4/11 ARV treatment facilities (36%) reported adverse reactions to the drug Acriptega. Among reported patients, 71% are men and 29% are women. Average age 47.6; average weight 55.6; The majority of reported subjects are people who have been on ARV treatment for a long time, accounting for 95%, with only 5% of people being new to ARV treatment; 9/21 people reported having comorbidities, of which hepatitis C accounted for the highest proportion, 33%. The reported adverse reactions of Acriptega were skin reactions in 14%, nephrotoxicity in 81% and hyperglycemia in 5%. 52% of reported cases were moderate; Mild levels account for 24%, 19% of severe levels and 5% of life-threatening levels. 48% of adverse reactions appeared after 12 months of using the drug, 38% appeared after 1-3 months and 14% appeared immediately after using the drug for less than 1 month. How to handle adverse reactions of the drug Acriptega: 95% switched regimen and 01 case/5% had to be transferred to a higher level. Of the patients who developed adverse reactions, 95% recovered without sequelae, but 10% died.
Keywords: adverse reactions; acriptega; Quang Ninh